Prevalence of actinic keratosis among dermatology outpatients in Austria. (1st December 2014) - Eder, J.; Prillinger, K.; Korn, A.; Geroldinger, A.; Trautinger, F.
Summary: Background: Actinic keratoses (AKs) are common precursors of squamous cell carcinomas (SCCs) of the skin making them an important public health issue with information on their prevalence widely lacking. Objectives: To define the prevalence of AK in dermatology outpatients in Austria and to identify more accurately the target population for AK screening, treatment and prevention. Methods: Each of the 48 randomly selected Austrian office‐based dermatologists simultaneously screened 100 consecutive patients (aged ≥ 30 years) for the presence of AK. Results: In total, 4449 evaluable patients showed an overall AK prevalence of 31·0%, which was higher in men (39·2%) than in women (24·3%) and increased with age in both sexes. AK distribution among sun‐exposed body sites and extent of disease varied with sex and region. Conclusions: In Austria, AKs are common among dermatology outpatients, who have access to professional education and treatment. Investigations regarding the efficacy of routine AK screening in dermatology outpatients for the prevention of invasive SCC is warranted.